2018
DOI: 10.1002/chem.201804025
|View full text |Cite
|
Sign up to set email alerts
|

Diphenylamine‐Substituted Osmanaphthalyne Complexes: Structural, Bonding, and Redox Properties of Unusual Donor–Bridge–Acceptor Systems

Abstract: Diarylamine‐substituted osmanaphthalyne complexes that feature two redox centers linked by the rigid skeleton of the metallacycle (C^C+), specifically, [OsCl2(PPh3)2{(C^C+)NAr2}][BF4−] (Ar=Ph (1 a), p‐MeOPh (1 b)) and their open‐ring precursors [OsHCl2(PPh3)2{(≡C−C(PPh3+)=CHPh)NR2}][BF4−] (Ar=Ph (2 a), p‐MeOPh (2 b)), were successfully synthesized and characterized by 1H, 13C, and 31P NMR spectroscopy, ESI‐MS, and elemental analysis. The solid‐state molecular structures of complexes 1 a and 2 a were ascertaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 118 publications
5
13
0
Order By: Relevance
“…In its 1 H NMR spectrum, a signal at δ ≈1.10 ppm may be ascribed to the trimethylphosphine protons, and a signal at δ =13.34 ppm in the 31 P{ 1 H} NMR spectrum may be attributed to the triphenylphosphonium group (PPh 3 + ). A signal at δ ≈267 ppm in the 13 C{ 1 H} NMR spectrum is close to those previously reported for cyclic metal carbynes [19–21] . Based on the reaction system and the results of elemental analysis and high‐resolution mass spectrometry, we preliminarily concluded that complex [ 1 (OCH 3 )]′ is the product of substitution of one triphenylphosphine ligand of complex 1 (OCH 3 ) by a trimethylphosphine ligand.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…In its 1 H NMR spectrum, a signal at δ ≈1.10 ppm may be ascribed to the trimethylphosphine protons, and a signal at δ =13.34 ppm in the 31 P{ 1 H} NMR spectrum may be attributed to the triphenylphosphonium group (PPh 3 + ). A signal at δ ≈267 ppm in the 13 C{ 1 H} NMR spectrum is close to those previously reported for cyclic metal carbynes [19–21] . Based on the reaction system and the results of elemental analysis and high‐resolution mass spectrometry, we preliminarily concluded that complex [ 1 (OCH 3 )]′ is the product of substitution of one triphenylphosphine ligand of complex 1 (OCH 3 ) by a trimethylphosphine ligand.…”
Section: Resultssupporting
confidence: 84%
“…The synthetic route to complex 1 (OCH 3 ) and its precursor 3 (OCH 3 ) is shown in Scheme 2 (Experimental Section). Complexes 1 (OCH 3 ) and 3(OCH 3 ) were both obtained as green solids, as reported in our previous publication [19] . The Os−H hydride ligand was confirmed by the signal of the chemical shift at −6.11 ppm in the 1 H NMR spectrum and the structure of the osmium carbyne was supported by the resonance at δ =250.4 ppm in the 13 C{ 1 H} NMR spectrum.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations